Rethinking the Biohazardous Bodily Fluids Alert for Improved Workflow and Safety - Patterson, Erica; Yan, Adam Paul; Silver, Shawna; Cardiff, Bren (Applied Clinical Informatics, 2025)
Ensuring clinician safety in health care settings is critical, particularly regarding exposure to hazardous drugs and bodily fluids, which can be carcinogenic, teratogenic, genotoxic, or cause organ toxicity at low doses. At SickKids a safety issue arose when a clinician was unknowingly exposed to hazardous bodily fluids due to inadequate communication of a patient's hazardous medication status.This clinical decision support (CDS) redesign aimed to reduce alert fatigue while ensuring timely team awareness to minimize hazardous bodily fluid exposure risk. This case study aims to explore how redesigning a CDS system addressed the dual challenge of maintaining safety communication while minimizing alert fatigue and improving workflow integration.In 2018, a biohazardous bodily fluids alert was introduced within the hospital's electronic patient record (EPR) to raise awareness. However, its frequent and disruptive nature resulted in a 0% alert action rate and 89 unactionable clinician hours over a 90-day period. Feedback collected over 42 months revealed clinician frustration and desensitization due to the alert's timing and frequency. Using a human-centered design approach, the alert was redesigned from an interruptive pop-up to a passive notification embedded within the patient's storyboard.The redesigned alert allowed clinicians to review hazardous status information without immediate interruptions, reducing workflow disruption while maintaining its critical safety function. This approach effectively balanced safety communication with clinicians' need for efficient workflows, addressing the root cause of alert fatigue.This case study highlights the importance of ongoing CDS evaluation and redesign to enhance clinician safety, minimize alert fatigue, and improve workflow integration. Future evaluations will assess the redesign's effect on personal protective equipment compliance and clinician burnout.
Keywords: alert fatigue; human-centered design; clinical decision support; usability; hazardous drug safety